Morphopathological Evaluation of Cortical Fibrosis and Extra-Renal Changes in Dogs with Chronic Kidney Disease - Pamu Sushma; Hamza Palekkodan; M.Pradeep; Chintu Ravishankar; Ajith Jacob George; R.Anoopraj; K.Krithiga; Pooja Kailas; Priya Dharshini (The Indian Veterinary Journal, 2026)
Chronic kidney disease (CKD) is a fatal disease in dogs characterized by progressive nephron loss. Cortical fibrosis serves as a key indicator of renal dysfunction. Although frequently observed, the literature on a systematic study of histological scoring of cortical fibrosis and associated extra-renal lesions in dogs is scarce. The present study screened the kidneys of 50 dog carcasses for gross and histologic changes of cortical fibrosis, along with the associated changes in liver and heart. The kidneys with cortical fibrosis were quantified using ImageJ software in picrosirius red-stained sections. Hepatic and cardiac tissues were examined histologically. The study revealed gross and histological lesions of cortical fibrosis in 15 dogs (30 %). On scoring, moderate cortical fibrosis was observed in 93.3 % (n=14) dogs, and marked fibrosis in 6.7 % (n=1) dog. Fibrosis severity was not influenced by age, sex, or breed. Four dogs (26.6 %) had cardiac lesions, mainly cardiomyocyte hypertrophy and arteriosclerosis. Combined cardiac and hepatic lesions, like mild peri-portal fibrosis and hepatic vacuolations, were observed in 5 cases (33.3 %) of moderate cortical fibrosis. The marked cortical fibrosis case also showed combined lesions (6.6 %) of other organs. Statistically, no significant correlation was observed across age, gender and breed-wise occurrence of CKD. The study revealed a higher occurrence of chronic kidney disease in dogs with a comparatively greater association with cardiac lesions.